Factors to Improve Fishery Household Welfare: Empirical Analysis of Indonesia - Wicaksono, Bayu Rhamadani; Yuniarti, Yuniarti; Paramartha, Dede Yoga (Economics and Finance in Indonesia, 2021)
This study attempts to verify the linkage between the characteristics of fishers and the welfare of fishery household in Indonesia, which is explained by the surplus obtained by fishers. Based on the empirical results using multiple linear regression analysis, variables with significant impacts on improving the welfare of fishery household in Indonesia in both marine and inland open water fisheries are fishing gear, number of fishers, number of crew, salary, province, age, gender, education level, processed storage, transportation, and market target. Furthermore, the characteristics of fishers are divided into similarities and differences. Observed from the similarities, the main fishers play a prominent role to fulfill the daily needs of their families. Observed from the differences, fishers in marine fisheries prefer to use a boat with an inboard motor, prepare more funds, and require more crew members because they usually catch fish on long trips. On the other hand, fishers in inland open water fisheries prefer to use a boat without an inboard motor, prepare less funds, and require less crew members because they usually catch fish on short trips. The government needs to formulate effective, efficient, and targeted policies for the welfare of fishers. The findings suggest several policy recommendations related to the improvement of fishery household welfare in Indonesia, such as soft loan in the form of People Business Credit (KUR), storage facilities for a better supply chain, and revitalization of fish auction sites.